Comparison of Routing Protocols and Communication Interfaces for the Implementation of Collision Avoidance Capabilities in Fleets of Industrial Mobile Robots. Issue 38 (2022) - Bonetti, Alessandro; Sabattini, Lorenzo
Abstract: In this paper a novel approach to a collision avoidance system between forklifts based on a wireless communication is proposed in order to test its performance and feasibility. First of all an overview on collision avoidance systems between vehicles inside warehouses is introduced with their main advantages and disadvantages. Then the reasons that led to the study of the new solution proposed in this article are motivated. Subsequently, a brief survey on mobile ad hoc networks and their main routing protocols that allow multi-hop communication is presented. For the implementation of the simulations OMNeT++ and SUMO software were used, which allowed to develop the model and the warehouse scenarios. Furthermore, we report the collision avoidance algorithm used in this study for the generation of a plausible network data load in order to collect and analyze simulation statistics. In particular, two applications have been developed, DiscoveryApp and AnticollisionApp, which are run by each node. Several simulations were then carried out, varying the size of the scenario, the communication interface standards and the routing protocols. In particular, communication interfaces based on the IEEE 802.15.4 and 802.11g standards and AODV, DSDV, GPSR routing protocols were tested. The last part of the paper concerns the analysis of the results based on the metrics of average end to end delay, overhead, average goodput and packet delivery ratio in order to determine the best combination of technologies for an application of this type.